Usage of a Senggani Fruit Vinegar (Melastoma Affine D. Don), to Improve Feed Efficiency and Lower Blood Glucose Levels in Hyperglycemia white Rats (Rattus Norvegicus L.) - Safrida Safrida; Raissya Adinda; Muhibbudin Muhibbudin; Khairil Khairil; M.D Asiah; Fitrah Asma Ulhusna (Jurnal Penelitian Pendidikan IPA, 2023)
Pancreatic beta cells may suffer harm as a result of hyperglycemia. This study examined the effect of Senggani fruit vinegar on blood sugar levels in hyperglycemic white rats. Conditions associated with hyperglycemia may result in an abundance of free radicals, a lack of antioxidants, and damage to pancreatic beta cells. One category of reactive oxygen species (ROS) are the free radicals produced by hyperglycemia. Because the senggani fruit's flavonoids have strong antioxidant properties, they can reduce blood sugar levels. Using a completely randomized design, which was divided into 6 treatments and 4 repeats, this research was applied to the experimental approach. The Variant Analysis algorithm was used to analyze the study's data (ANOVA). Blood glucose levels were among the variables measured. gathered information that explains how giving rats vinegar made from the senggani fruit lowers their blood sugar levels. It is evident that the administration of senggani fruit vinegar (Melastoma affine D. Don) has a positive impact on lowering blood glucose levels in hyperglycemia in white rats (Rattus norvegicus L.).